1989
DOI: 10.1128/jb.171.2.775-783.1989
|View full text |Cite
|
Sign up to set email alerts
|

Nucleotide sequence of Escherichia coli isochorismate synthetase gene entC and evolutionary relationship of isochorismate synthetase and other chorismate-utilizing enzymes

Abstract: Biochemical analysis of the enzymatic activity catalyzing the conversion of chorismate to isochorismate in the enterobactin biosynthetic pathway attributed the reaction to the isochorismate synthetase enzyme, designated EntC. However, the lack of mutations defining this activity has hampered the precise identification of the entC structural gene. In this study, we engineered a stable insertion mutation into the chromosomal region between the enterobactin genes fepB and entE. This mutation disrupted the structu… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

3
81
0

Year Published

1991
1991
2012
2012

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 118 publications
(84 citation statements)
references
References 33 publications
3
81
0
Order By: Relevance
“…Walsh and coworkers (39,40), Earhart and coworkers (41,42), and McIntosh and coworkers (43,44) have shown that enterobactin is synthesized from a fork in the aromatic amino acid pathway in a two-step process (40,41,45). Chorismic acid, an aromatic amino acid precursor, is converted into isochorismate, then into 2,3-dihydro-2,3-dihydroxybenzoate, and finally into 2,3-dihydroxybenzoic acid (DHB).…”
Section: Biosynthesis Of Enterobactinmentioning
confidence: 99%
“…Walsh and coworkers (39,40), Earhart and coworkers (41,42), and McIntosh and coworkers (43,44) have shown that enterobactin is synthesized from a fork in the aromatic amino acid pathway in a two-step process (40,41,45). Chorismic acid, an aromatic amino acid precursor, is converted into isochorismate, then into 2,3-dihydro-2,3-dihydroxybenzoate, and finally into 2,3-dihydroxybenzoic acid (DHB).…”
Section: Biosynthesis Of Enterobactinmentioning
confidence: 99%
“…These include pheA (chorismate mutase-prephenate dehydratase), tyrA (chorismate mutase-prephenate dehydrogenase) (10), entC (isochorismate synthase) (23), pabA and pabB (4-amino-4-deoxychorismate synthase) (6,12), pabC (4-amino-4-deoxychorismate lyase) (7), and trpE and trpD (anthranilate synthase-5-phosphoribosyl-1-pyrophosphate phosphoribosyl transferase) (20,22). * Corresponding author.…”
mentioning
confidence: 99%
“…In E. coli, the region between the fepB and entC genes is approximately 370 bp, which contains the fepB and entC promoters (6,13,31). These (35).…”
Section: Discussionmentioning
confidence: 99%
“…Transcription of the enterobactin genes, which is regulated by the product of the fur gene and intracellular iron, initiates from two sets of tandem promoters situated between the fepA and fes genes (37,38) and between fepB and entC (13,31). It is likely that additional promoters exist.…”
mentioning
confidence: 99%
See 1 more Smart Citation